L'âge du Fer dans le haut Jura Les tumulus de la région de Pontarlier (Doubs) - Bichet, Pierre (Documents d'archéologie française, 1992)
Only perceptable to the averted eye due to their low relief, the barrows of Chaux d'Arlier have remained little known until the first surveys were carried out during the period 1950-60. Although saved front unscientific excavation, they have however not escaped damage from agricultural practice or its modernisation. Presented in this publication are the results from recent rescue excavations which outline the importance of later prehistoric occupation in this traditional area of contact. Put at the disposition of the reader, is a documentation of an interest which justifies the measures taken to protect these monuments.